Deep neural network-based approach to improving radiomics analysis reproducibility in liver cancer: effect on image resampling. (19th August 2021) - Yang, Pengfei; Xu, Lei; Wan, Yidong; Yang, Jing; Xue, Yi; Jiang, Yangkang; Luo, Chen; Wang, Jing; Niu, Tianye
Abstract: Objectives. To test the effect of traditional up-sampling slice thickness (ST) methods on the reproducibility of CT radiomics features of liver tumors and investigate the improvement using a deep neural network (DNN) scheme. Methods. CT images with ≤ 1 mm ST in the public dataset were converted to low-resolution (3 mm, 5 mm) CT images. A DNN model was trained for the conversion from 3 mm ST and 5 mm ST to 1 mm ST and compared with conventional interpolation-based methods (cubic, linear, nearest) using structural similarity (SSIM) and peak-signal-to-noise-ratio (PSNR). Radiomics features were extracted from the tumor and tumor ring regions. The reproducibility of features from images converted using DNN and interpolation schemes were assessed using the concordance correlation coefficients (CCC) with the cutoff of 0.85. The paired t-test and Mann–Whitney U test were used to compare the evaluation metrics, where appropriate. Results. CT images of 108 patients were used for training ( n  = 63), validation ( n  = 11) and testing ( n  = 34). The DNN method showed significantly higher PSNR and SSIM values ( p  < 0.05) than interpolation-based methods. The DNN method also showed a significantly higher CCC value than interpolation-based methods. For features in the tumor region, compared with the cubic interpolation approach, the reproducible features increased from 393 (82%) to 422(88%) for the conversion of 3–1 mm, and from 305(64%) to 353(74%) for the conversion of 5–1 mm. For features in the tumor ring region, the improvement was from 395 (82%) to 431 (90%) and from 290 (60%) to 335 (70%), respectively. Conclusions. The DNN based ST up-sampling approach can improve the reproducibility of CT radiomics features in liver tumors, promoting the standardization of CT radiomics studies in liver cancer.